International trade and Climate Change : Economic, Legal, and Institutional Perspectives - World Bank (Washington, DC: World Bank, 2012)
The broad objective of this study is to analyze areas in which the climate change agenda intersects with multilateral trade obligations. The study identifies the key issues at stake, as well as possible actions -- at the national and multilateral levels -- that could help developing countries strengthen their capacities to respond to emerging conflicts between international trade and global climate regimes while taking advantage of new opportunities. The study also attempts to respond to the need for more sector-specific analysis. Chapter two contributes to the literature by exploring the economic, environmental, and political rationale underlying the potential tension between implementation of the Kyoto Protocol and the existing World Trade Organization (WTO) principles. The chapter further identifies areas where priorities for proactive policy initiatives could minimize potential damage to both trade and global environmental regimes. Chapter three explores and identifies key barriers and opportunities to spur the transfer and diffusion of climate-friendly and clean-energy technologies in developing countries. It further identifies policies and institutional changes that could lead to the removal of barriers and increased market penetration of climate-friendly technology. Chapter four examines and builds on the different approaches that have emerged in the negotiations surrounding trade in environmental goods and services, and it proposes a framework for integrating climate objectives in the discussions. Chapter five presents the conclusions and provides a framework for integrating and streamlining the global environment within the global trading system.